Juridical Study of Criminal Law on Delegation of Authority of Obstetricians and Gynecologists to Midwives in Health Services - Damayanti, Fitriani Nur; Mulyanti, Lia; Poddar, Sandeep (Jurnal Hukum Novelty, 2023)
Introduction to the Problem: The entitlement to health services represents an inherent right accorded to each citizen within the Indonesian jurisdiction. Within this framework, health practitioners assume a pivotal role in augmenting the optimal provision of healthcare to the populace. Specifically, midwives play a critical function in delivering health services aligned with the directives of medical professionals, particularly in exigent situations and referral services. The legal ramifications surrounding a midwife's engagement in illicit childbirth practices underscore the imperatives of statutory compliance. Within the confines of the Penal Code, responsibility is construed as an imperative, denoting that transgressions of criminal statutes necessitate accountability in accordance with the prescribed legal provisions.Purpose/Objective Study: This study seeks to elucidate the juridical examination of the delegation of authority within the realm of healthcare services, specifically focusing on the intricate dynamics between medical practitioners and midwives.Design/Methodology/Approach: The employed research methodology involves normative juridical analysis utilizing secondary data. Within the purview of this investigation, the research framework adheres to legal principles, encompassing an examination of both codified positive law and uncodified positive law.Findings: The delegation of authority upon midwives to execute health service activities is predicated upon a mandate from doctors, necessitating recurrent monitoring and evaluation by the medical practitioners. This delegation of authority pertaining to health-related responsibilities to midwives is effectuated through both written documentation and oral communication via telephone. The locus of responsibility for this delegation rests with the healthcare institution, where physicians assume the role of conferring authority, and midwives act as the executors entrusted with such delegated responsibilities.Paper Type: Research Article